Pelaksanaan Program KINERJA Dalam Hubungan Kerjasama Antara Pemerintah Provinsi Jawa Timur Dengan United States Agency For International Development Tentang Perbaikan Iklim Usaha Melalui Pelayanan Perizinan Terpadu Satu Pintu - Aditya Fajrul Ahmad Adji (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2015)
Abstract:Implementation Program of KINERJA In Cooperation Relations Between Government of East Java Province with the United States Agency for International Development About Business Climate Improvement Through Licensing One Stop Services (Study on Investment and Licensing Office Probolingg). Provinsi Jawa Timur mention a few priorities and direction of development policy whose aim is to improve the business climate/investment by the empowerment of cooperatives, micro, small and medium enterprises. In order to improve the business climate, East Java Provincial Government to build a relations of cooperation with international institutions United States Agency for International Development (USAID) with the involvement local government of Probolinggo. In this cooperation relations, USAID created a program, called program